Analysis of potential environmental impacts in the coffee supply chain using the Life Cycle Impact Assessment - Nurul Chairany; Phirros Arifan Taufik; Taufik Nur; Andi Pawennari (Center for Science and Technology, IAIN Surakarta, 2024)
Agroindustry refers to industry that process agricultural raw materials into value-added products. Sanrego coffee is a blend of authentic Sanrego coffee and sugar, without the use of chemicals. SMI Sanrego Caffee produces a variety of products, including coffee and chocolate. However, the coffee processing activities at SMI Sanrego Caffee can have potential environmental impacts due to emissions, liquids waste, and solid waste generation. to assess and mitigate these environmental impacts, the Life Cycle Assessment (LCA) method is amployed. LCA evaluates the environmental effects at various stages of a product, process, or service lifecycle. Based on the results from the analysis, using the Simapro software, the potential environmental impacts were compared across several impact categories, abiotic depletion (3.77 kg Sb-eq), global warming (518 kg CO2-eq), acidification (4.41 kg SO2-eq). The interpretation stage of the analysis identified several areas improvement: first, optimizing fuel usage; secondly, reducing reliance on aluminum foil; third, minimizing the use of sacks; and lastly, reducing electricity consumption.